Pengaruh Kemandirian Belajar Terhadap Kemampuan Penalaran Matematis Materi Barisan Dan Deret Di Masa Pandemi COVID-19 - Solatiah Ariani; Sudi Prayitno; Ratna Yulis Tyaningsih; Arjudin Arjudin (Griya Journal of Mathematics Education and Application, 2022)
This research aimed to describe students self-regulated learning and mathematical reasoning ability as well as to know the significant effect of self-regulated learning on the mathematical reasoning ability about sequence and series subject for students grade XI of SMAN 1 Keruak during the COVID-19 pandemic. The research method uses the corelasional method. The research instrument was a self-regulated learning questionnaire and mathematical reasoning ability test. Data analysis technique using simple linear regression analysis. The results of this study indicate that: (1) Descriptively from the data on the self-regulated learning of grade XI SMA Negeri 1 Keruak students are in the medium category that is 64,5%; (2) Descriptively from the data on the mathematical reasoning ability of grade XI SMA Negeri 1 Keruak students are in the medium category that is 54,8%; (3) There is a significant effect self-regulated learning on the mathematical reasoning ability about sequence and series subject for students grade XI of SMAN 1 Keruak during the COVID-19 pandemic. This is in accordance with the results of the regression aquation Y = 18,671+ 0,715 X and the results of the F test calculations which show that . The contribution of self-regulated learning to students mathematical reasoning ability is 40,8% and the remaining 59,2% is influenced by other factorsThis research aimed to describe students self-regulated learning and mathematical reasoning ability as well as to know the significant effect of self-regulated learning on the mathematical reasoning ability about sequence and series subject for students grade XI of SMAN 1 Keruak during the COVID-19 pandemic. The research method uses the corelasional method. The research instrument was a self-regulated learning questionnaire and mathematical reasoning ability test. Data analysis technique using simple linear regression analysis. The results of this study indicate that: (1) Descriptively from the data on the self-regulated learning of grade XI SMA Negeri 1 Keruak students are in the medium category that is 64,5%; (2) Descriptively from the data on the mathematical reasoning ability of grade XI SMA Negeri 1 Keruak students are in the medium category that is 54,8%; (3) There is a significant effect self-regulated learning on the mathematical reasoning ability about sequence and series subject for students grade XI of SMAN 1 Keruak during the COVID-19 pandemic. This is in accordance with the results of the regression aquation Y = 18,671+ 0,715 X and the results of the F test calculations which show that . The contribution of self-regulated learning to students mathematical reasoning ability is 40,8% and the remaining 59,2% is influenced by other factors